(untitled) (Third Sector Social Economic Review, 2019)
This paper is a study showing the support of aquaculture production in our country and the effects of these supports on this production. The article includes practical information such as the contents of the loans that encourage production under the main headings, where they can be obtained and who can benefit from them. Texts are enriched with tables, figures and tables to better understand the subjects. It is considered to be a guiding source for loans given in the field of aquaculture production in Turkey. “Lending” in Turkey’s aquaculture production is considered to be extremely important for production due to the relatively low number of studies; sustainability is considered to be the contribution of support implemented in Turkey.